Aeolian dune sediment flux variability over an annual cycle of wind. Issue 6 (October 2016) - Swanson, Travis; Mohrig, David; Kocurek, Gary
Abstract: Aeolian dune motion is thought to be driven by an annual cycle of sediment‐transporting wind events. Each wind event drives uneven motion of dune crestlines, yet dune crestlines align as a trend to an annual cycle of wind. Understanding the variability in dune motion over such a cycle aids the interpretation of aeolian cross‐stratification, often available only in the limiting exposure of core and outcrop. Digital elevation models obtained by light detection and ranging are used to estimate dune brink motion and sediment flux along the sinuous crestlines of crescentic dunes at White Sands gypsum dune field (south‐central New Mexico, USA) over an annual cycle of wind. In tandem, meteorological observations over the same annual cycle are used to drive a kinematic model of dune crestline motion. Wind‐driven kinematic modelling does well to predict the mean and overall variation in sediment flux with compass direction. Digital elevation model‐based estimations of brink motion and sediment flux reveal that dune motion and sediment flux very nearly follow a circular normal distribution. Dunes at White Sands were found to achieve steady mean values of lee surface dip direction, brink motion and sediment flux within a sample window the size of approximately six dunes of average crestline length. Due to the symmetrical distribution of dune motion about the average lee surface dip direction, uneven motion of dune crestlines averages to become motion of dune crestlines normal to a trend, as predicted by wind‐driven kinematic models.